Prospective international multicenter pectopexy trial: Interim results and findings post surgery. (January 2020) - Noé, Günter K.; Schiermeier, Sven; Papathemelis, Thomas; Fuellers, Ulrich; Khudyakov, Alexander; Altmann, Harald-Hans; Borowski, Stefan; Morawski, Pawel P.; Gantert, Markus; De Vree, Bart; Zbigniew, Tkacz; Ugarteburu, Rodrigo Gil; et al.
Abstract: The technique of laparoscopic pectopexy was published in 2010. A subsequent randomized trial focused on pectopexy versus sacropexy revealed no new risks for patients and significant advantages in terms of operating time and de novo defecation disorders compared to sacrocolpopexy. The present international multicenter trial was performed to evaluate the applicability of the technique in clinical routine. Material and Method: Eleven clinics and 13 surgeons in four European counties participated in the trial. To ensure a standardized approach and obtain comparable data, all surgeons followed the same rules in placing the apical tape, no further mesh was used. Data were collected for 14 months on a secured server; 501 surgeries were documented and evaluated. Results: Patients treated at the leading center (2 surgeons) contributed 44 % of the patient population. We made a distinction between high-volume (48–135 surgeries annually) (n = 4), intermediate-volume (28–37 surgeries annually) (n = 4), and low-volume (7–22 surgeries annually) (n = 5) surgeons. 97.3 % of the patients (n = 501) had delivered children; 5.6 % had had a Caesarian section. 29.7 % of the patients had undergone a hysterectomy. The operating time for pectopexy was less than 60 min in 79 % of cases. The procedures were completed in less than 159 min in 71 % of cases. Severe complications (n = 5) included four cases of organ damage (related to concomitant surgeries or adhesions) and one case of relevant bleeding. De novo incontinence was registered in two cases and voiding dysfunction in three. No intestinal obstruction or defecation disorder was observed. Two complicated infections were noted. Urinary infection occurred in 2 % of patients. Conclusion: In clinical routine severe complications occurred in 1 %. The latter were unrelated to pectopexy, but occurred due to concomitant procedures or adhesions. The overall operating time as well as the operating time for pectopexy were similar to those reported in published studies on sacrocolpopexy.